Trans -splicing enhances translational efficiency in C. elegans - Yang, Yu-Fei; Zhang, Xiaoqing; Ma, Xuehua; Zhao, Taolan; Sun, Qiushi; Huan, Qing; Wu, Shaohuan; Du, Zhuo; Qian, Wenfeng (Genome research, 2017)
Translational efficiency is subject to extensive regulation. However, the factors influencing such regulation are poorly understood. In Caenorhabditis elegans , 62% of genes are trans- spliced to a specific spliced leader (SL1), which replaces part of the native 5′ untranslated region (5′ UTR). Given the pivotal role the 5′ UTR plays in the regulation of translational efficiency, we hypothesized that SL1 trans- splicing functions to regulate translational efficiency. With genome-wide analysis on Ribo-seq data, polysome profiling experiments, and CRISPR-Cas9–based genetic manipulation of trans- splicing sites, we found four lines of evidence in support of this hypothesis. First, SL1 trans- spliced genes have higher translational efficiencies than non- trans- spliced genes. Second, SL1 trans- spliced genes have higher translational efficiencies than non- trans- spliced orthologous genes in other nematode species. Third, an SL1 trans- spliced isoform has higher translational efficiency than the non- trans- spliced isoform of the same gene. Fourth, deletion of trans -splicing sites of endogenous genes leads to reduced translational efficiency. Importantly, we demonstrated that SL1 trans- splicing plays a key role in enhancing translational efficiencies of essential genes. We further discovered that SL1 trans- splicing likely enhances translational efficiency by shortening the native 5′ UTRs, hence reducing the presence of upstream start codons (uAUG) and weakening mRNA secondary structures. Taken together, our study elucidates the global function of trans- splicing in enhancing translational efficiency in nematodes, paving the way for further understanding the genomic mechanisms of translational regulation.